Fair allocation of cost reductions for a scale-based product family in a hierarchically structured firm. (2017) - Mueller, David
Size ranges are a widespread type of product family design, which are used to combine high product variety and cost reductions. For the purposes of motivation and remuneration, these cost reductions should be shared in a fair way between the employees. The nature of cooperative cost reductions is super-additive - a fact which impedes a fair assignment. For this reason, the purpose of this paper is to present an approach for calculating and fairly allocating a cost reduction in a hierarchically structured firm. The process of designing and producing size ranges is modelled as a cost-reduction game within a hierarchically structured organisation. Assuming a hierarchical organisation, this study presents a mechanism which distributes this cost reduction across all contributing employees in the firm. The research shows that cost growth laws are suitable for calculating the costs of all members of a product family based on the basic draft using physical characteristics.